The role of academic procrastination on Internet addiction among Thai university students: A cross-sectional study - Sivasankari Nadarajan; Pornpat Hengudomsub; Chintana Wacharasin (Belitung Raya Foundation, Indonesia, 2023)
Background: The internet has become an inevitable tool for information-seeking and communication in today’s modern era. However, ironically it has driven humankind to become more dependent, leading to addiction. Internet addiction has increased exponentially at all levels of society, especially university students, impeding their physical, psychological, and social well-being. Objective: This study aimed to examine the relationship between academic procrastination and internet addiction and determine the influence of academic procrastination on internet addiction among Thai university students. Methods: A cross-sectional study was conducted involving 470 participants selected through multi-stage cluster random sampling from a university in eastern Thailand. The data collection was conducted between 29 November 2022 and 27 January 2023. The data were gathered using a demographic data form, an internet addiction test, and a procrastination assessment scale for the students’ questionnaire. Descriptive statistics, Pearson correlation coefficient, and simple linear regression were employed for data analysis. Results: The results revealed that academic procrastination (M = 49.68, SD = 12.61) and internet addiction (M = 65.26, SD = 5.60) were at a moderate level. A positive correlation was identified between academic procrastination and internet addiction (r = 0.33, p <0.01), indicating a low relationship. Academic procrastination also had a significant predictive power on internet addiction, accounting for 11.3% of the variance (R2 adjusted = 0.113, F (1, 468) = 59.583, p <0.001). Conclusion: The findings indicated the significant role of academic procrastination on internet addiction. Therefore, it is crucial that nurses should formulate interventions by considering this factor and emphasize self-regulatory and time-management skills and practical ways to limit internet dependence. Furthermore, the findings suggest that nurses could assess the procrastination level among students, devise prevention strategies, and organize awareness campaigns to instill information about rational internet use that aids in mitigating the risks and preventing them from getting addicted.